The Role of Landscape Architecture Profession In Two Different Contexts: A Comparative Review of the Practitioners in Responding To Climate Change Adaptation - Mildawani, Irina; Khan, Shahed (Department of Urban and Regional Planning, Diponegoro University, 2014)
Abstract: In the context of rising concerns about global warming and sustainable development this paper examines the challenges of landscape architecture (LA) in developing and developed countries in handling climate change adaptation. The paper aims to find how the LA institutes define their professionalsâ roles in dealing with society and environment. It seeks to focus on the professionalsâ involvement in climate change adaptation programs in Indonesia and Australia. The paper seeks to determine how contextual factors such as institutional roles and types of prevalent governance systems shape the development of landscape architecture discipline and its professional capability with respect to other related built environment professions (architecture and planning). The websites of the ISLA (Indonesian Society of Landscape Architects) and the AILA (Australian Institutes of Landscape Architects) are examined and analysed from the perspective of professional principles of the International Federation of Landscape Architects (IFLA). The aim is to determine the LA practitionersâ awareness and approaches in handling climate change challenges in various roles and capabilities. It has found that the professional institute in Australia has been involved in the educational program to equip their practitioner members to have a basic knowledge and further application of climate change adaptation in their design and planning projects; whereas in Indonesia the practitioners are actively involved in community capacity building to increase peopleâs awareness and participation in mitigating the climate change at local as well as regional levels. Findings from the study seek to establish the universality of the LA profession and its relevance in both developed and developing countries.Keywords: climate change adaptation network, IFLA principles, ISLA and AILA, landscape architecture profession